2020
DOI: 10.1088/2053-1591/ab69c7
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and mechanical properties of Ni60 alloy fabricated by laser metal deposition

Abstract: Due to its low melting point and high hardness, Ni60 (Ni-Cr-B-Si) alloy is widely used as surface cladding material for mould steel. In present study, Ni60 alloy thin-walled samples were fabricated using laser metal deposition (LMD) technology on H13 steel substrate which is usually used as mould material. The microstructure and mechanical properties (microhardness and wear resistance) of LMD Ni60 alloy were investigated. The results show that the LMD Ni60 alloy sample is mainly composed of Ni, Ni 3 Fe, Ni 3 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…In our previous research, the Ni-Cr-B-Si alloy tends to form large amount of Ni columnar dendrites and Cr precipitate dendrites during LMD [14]. And there are continuous eutectic structures between the dendrites and Cr hard phases.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In our previous research, the Ni-Cr-B-Si alloy tends to form large amount of Ni columnar dendrites and Cr precipitate dendrites during LMD [14]. And there are continuous eutectic structures between the dendrites and Cr hard phases.…”
Section: Introductionmentioning
confidence: 88%
“…It is widely used in applications requiring high hardness and wear resistance [2]. In recent years, researches on the alloys are mainly concentrated on laser cladding [2][3][4][5][6][7][8][9], while there are few reports about 3D printing [10][11][12][13][14]. With the development of additive manufacturing technology, Ni-Cr-B-Si alloy has a good potential in the field of repairing and free-form manufacturing [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the metal was transferred to a preheated ladle with a capacity of 70 kg, and the metal was poured into cone-shaped sand molds (Figure 2a). The dimensions of the The quantity and nature of the precipitates and eutectic phases are also affected by the cooling rate [13,19]. Wang et al [19] observed that, at a faster cooling rate, eutectics take a larger proportion; meanwhile, Cr-rich precipitates are refined and dispersed uniformly.…”
Section: Casting Processmentioning
confidence: 99%
“…The common coating techniques used for these alloys are flame spraying [3][4][5][6], plasma spraying [7][8][9], high-velocity oxygen fuel spraying (HVOF) [10][11][12], laser cladding [13][14][15][16][17], laser metal deposition (LMD) [18,19], non-vacuum electron beam cladding [20,21], laser powder bed fusion (LPBF) [22], and the plasma transferred arc welding (PTAW) processes [23]. All of these techniques have high solidification rates that can lead to different types of defects, and they can also enhance the porosity and cracking susceptibility of these materials [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation